2014
DOI: 10.1177/1932296814522809
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pump Patient Characteristics and Glucose Control in the Hospitalized Setting

Abstract: Patients' knowledge of their insulin pumps and glucose control during hospitalization has not been studied. The aim was to study the determinants of glycemic control in patients using continuous subcutaneous insulin infusion (CSII) in the hospital. Three groups of patients were identified: those who did not need any inpatient education and continued on CSII (gorup A), those who received education then continued on CSII (group B), and those for whom CSII was not appropriate and were treated with multiple daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 10 publications
0
20
0
2
Order By: Relevance
“…There were no differences in the mean daily glucose levels; however, there were significantly fewer episodes of severe hyperglycemia (glucose >350 mg/dL [19.4 mmol/L]) and hypoglycemia (glucose <40 mg/dL [2.2 mmol/L]) in those who continued CSII compared with those taken off the pump (32). Similarly, a more recent study on 50 patients with 51 hospital admissions, 86% of whom had T1D, also reported no differences in mean blood glucose (BG), frequency of hyperglycemia, or hypoglycemic events among patients treated with CSII compared with those who were transitioned to a multiple daily injection (MDI) regimen (33). The authors concluded that with appropriate patient selection and usage guidelines, most patients using insulin pumps could safely have their therapy transitioned to the inpatient setting.…”
Section: Insulin Pump Use In the Hospitalmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no differences in the mean daily glucose levels; however, there were significantly fewer episodes of severe hyperglycemia (glucose >350 mg/dL [19.4 mmol/L]) and hypoglycemia (glucose <40 mg/dL [2.2 mmol/L]) in those who continued CSII compared with those taken off the pump (32). Similarly, a more recent study on 50 patients with 51 hospital admissions, 86% of whom had T1D, also reported no differences in mean blood glucose (BG), frequency of hyperglycemia, or hypoglycemic events among patients treated with CSII compared with those who were transitioned to a multiple daily injection (MDI) regimen (33). The authors concluded that with appropriate patient selection and usage guidelines, most patients using insulin pumps could safely have their therapy transitioned to the inpatient setting.…”
Section: Insulin Pump Use In the Hospitalmentioning
confidence: 99%
“…Reasons for discontinuing pump therapy at the time of admission were lack of additional pump supplies, threats of suicide or actual suicide attempts, malfunction of the pump, and altered level of consciousness. In a different study, the reasons for CSII discontinuation included patient preference, inability to safely demonstrate pump settings, and inexperience owing to recent initiation of CSII, while inability to correctly demonstrate appropriate pump settings, lack of family support, and postoperative mental status precluded restarting use of the insulin pump upon discharge (33).…”
Section: Insulin Pump Use In the Hospitalmentioning
confidence: 99%
See 1 more Smart Citation
“…As with insulin pumps, 25 patients and providers will have varying knowledge of the capability and limitations of these devices. Thus, institutions need to set policies for safe management, 26 if they are to be allowed at all.…”
Section: Evidence For Inpatient Cgmmentioning
confidence: 98%
“…The largest series ( n = 164 admissions) found no surgical site infections, mechanical failures, or hospital-acquired diabetic ketoacidosis[15,16]. Both retrospective studies and a single, small randomized trial suggest that when compared to usual care, inpatient CSII use is equivalent for hyperglycemia events and possibly superior in hypoglycemia prevention[17,18].…”
Section: Outpatient Technologies Adapted For Inpatient Use Csiimentioning
confidence: 99%